(untitled) (The Research of Medical Science Review, 2025)
This article discusses the concept of biomarkers in toxicogenomics and focuses on their roles in explaining biological effects of toxic compounds at the molecular level. Biomarkers are significant indicators in exposure, effect, and susceptibility that allow prediction and evaluation of adverse outcomes. The advanced toxicogenomics has made this biomarker crucial in identifying the interaction between genes and their environment, risk assessment, and development of targeted interventions. This review article identifies the kinds of biomarkers, such as genomic, proteomic, and metabolomic markers, and potential applications of these in understanding the pathways of toxicity and variability between individuals in response to toxicants. Therefore, this study integrates cutting-edge technologies to underscore the important role that biomarkers play in moving toward precision medicine and improving our ability to mitigate environmental and pharmaceutical risks.